2013
DOI: 10.1371/journal.pone.0081165
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic Effects of the Snake Venom Disintegrin Saxatilin Determined by Novel Assessment Methods: A FeCl3-Induced Thrombosis Model in Mice

Abstract: Saxatilin, a novel disintegrin purified and cloned from the venom of the Korean snake Gloydius saxatilis, strongly inhibits activation and aggregation of platelets. Glycoprotein (GP) IIb/IIIa receptor antagonists can resolve thrombus, so saxatilin might also have thrombolytic effects. We investigated the thrombolytic effects of saxatilin in mice using a ferric chloride-induced carotid arterial thrombosis model. Thrombotic occlusion and thrombus resolution were evaluated quantitatively by measuring blood flow i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 43 publications
(49 reference statements)
1
27
0
Order By: Relevance
“…In addition, the process of thrombus dissolution during thrombolytic treatment may be dynamic, with frequent thrombolysis and rethrombosis occurring during or immediately after thrombolytic treatment. 16,33 This was also observed during the real-time monitoring of blood flow in the mice in our experimental study, with frequent alternate reocclusion and reperfusion during or immediately after tPA infusion. Therefore, the thrombus volume, which was measured based on a onetime snapshot CT image, may be insufficient for assessing the entire process of thrombus dissolution after tPA treatment.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…In addition, the process of thrombus dissolution during thrombolytic treatment may be dynamic, with frequent thrombolysis and rethrombosis occurring during or immediately after thrombolytic treatment. 16,33 This was also observed during the real-time monitoring of blood flow in the mice in our experimental study, with frequent alternate reocclusion and reperfusion during or immediately after tPA infusion. Therefore, the thrombus volume, which was measured based on a onetime snapshot CT image, may be insufficient for assessing the entire process of thrombus dissolution after tPA treatment.…”
Section: Discussionsupporting
confidence: 73%
“…25 We have previously shown that the size of thrombus formed by FeCl 3 treatment was similar among animals in this model and that the degree of blood flow restoration, as measured by ultrasound, is a good representation of thrombus resolution. 16 Although it has been suggested that an aged thrombus would be resistant to tPA treatment, this concept remains understudied in vivo. 10 This study, using a thrombosis model in mice, clearly demonstrated that the effect of tPA is dependent on the age of the thrombus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations